Identification of Natural Red Dyes in 15-17th Centuries Ottoman Silk Textiles (Kaftans, Brocades, Velvets and Skullcaps) by HPLC with Diode Array Detection - Karadag, R.; Yurdun, T.; Dolen, E. (Asian Journal of Chemistry, 2010)
The high performance liquid chromatography (HPLC) with diode array detection (HPLC-DAD) method was utilized for the identification of dyestuffs of different insect dyes Ararat kermes, cochineal, Mediterranean kermes, lac and dye plant madder the most important natural red dyes found in historical textiles. Reversed-phase HPLC with diode-array detection has been used for identification of natural dyes in extracts of historical silk art objects, from historical textiles and newly dyed silk and wool fibres. The objects examined originate from 15-17th century Ottoman period and belong to the collection of the Topkapi Palace Museum in Istanbul. Fibres with only a red colour were selected for the analysis. Extraction from silk fibres was carried out with HCl/ MeOH/H2O solution. Dye components were identified in the 13 art objects analyzed. Insect and plant dyes were found.